Does exposure to environmental radiofrequency electromagnetic fields cause cognitive and behavioral effects in 10‐year‐old boys?. Issue 1 (January 2016) - Calvente, Irene; Pérez‐Lobato, Rocío; Núñez, María‐Isabel; Ramos, Rosa; Guxens, Mònica; Villalba, Juan; Olea, Nicolás; Fernández, Mariana F.
Abstract : The relationship between exposure to electromagnetic fields from non‐ionizing radiation and adverse human health effects remains controversial. We aimed to explore the association of environmental radiofrequency‐electromagnetic fields (RF‐EMFs) exposure with neurobehavioral function of children. A subsample of 123 boys belonging to the Environment and Childhood cohort from Granada (Spain), recruited at birth from 2000 through 2002, were evaluated at the age of 9–11 years. Spot electric field measurements within the 100 kHz to 6 GHz frequency range, expressed as both root mean‐square (SRMS ) and maximum power density (SMAX ) magnitudes, were performed in the immediate surrounds of childreńs dwellings. Neurocognitive and behavioral functions were assessed with a comprehensive battery of tests. Multivariate linear and logistic regression models were used, adjusting for potential confounders. All measurements were lower than reference guideline limits, with median SRMS and SMAX values of 285.94 and 2759.68 μW/m 2, respectively. Most of the cognitive and behavioral parameters did not show any effect, but children living in higher RF exposure areas (above median SRMS levels) had lower scores for verbal expression/comprehension and higher scores for internalizing and total problems, and obsessive‐compulsive and post‐traumatic stress disorders, in comparison to those living in areas with lower exposure. These associations were stronger when SMAX values were considered. Although some of our results may suggest that low‐level environmental RF‐EMF exposure has a negative impact on cognitive and/or behavior development in children; given limitations in the study design and that the majority of neurobehavioral functioning tasks were not affected, definitive conclusions cannot be drawn. Bioelectromagnetics. 37:25–36, 2016. © 2015 Wiley Periodicals, Inc.